Uptake and Determinants of Tetanus Vaccination among Female Clinical Medical Students in North-Western Nigeria - Muhammad Shakur Abubakar (Archives of Medicine and Health Sciences)
Background and Aim: Neonatal and maternal tetanus have remained endemic in tropical countries of Asia and Africa, with high fatality. Vaccination of women of childbearing age is the main strategy for their prevention/elimination. However, the uptake of these vaccines among these women has remained dismally low in these parts of the world. This study looked at the uptake and determinants of tetanus vaccination among the female clinical medical students of Bayero University, Kano, purposely looking at the interplay between knowledge and other factors on vaccine uptake. Materials and Methods: This was a cross-sectional study of female medical students aged 15–45 years, selected using probability proportionate to size and simple random sampling. The required information was collected using a validated semi-structured questionnaire. The data were analyzed using the Statistical Product and Service Solutions (SPSS) for Windows version 23. Prevalences of tetanus vaccination were calculated. The presence of a statistically significant difference in prevalence and other characteristics of the study groups were determined using appropriate tests. P <0.05 was considered statistically significant. Results: The participants were 140 with the mean age and mean knowledge scores of 23.96 (±2.74) years and 6.61 (±2.47), respectively. Most of them (59.3%) had good knowledge score (>7). The prevalence of tetanus toxoid (TT)1 and TT2 was 20.7% and 17.1%, respectively. Being married, ever pregnant, and higher level of study were significantly associated with being vaccinated (χ2/P =59.093/P <0.001, P = 65.011/P <0.001, and P = 9.860/P =0.020, respectively). Conclusions: Despite the good knowledge of the vaccination, the uptake of TT vaccination among clinical female students was poor. Factors significantly associated with higher vaccine uptake were marital status, age of the participants, and their class of study.